Enablers of the successful implementation of simulation exercises: a qualitative study among nurse teachers in undergraduate nursing education - Kristine Haddeland; Åshild Slettebø; Mariann Fossum (BMC, 2021)
Abstract Background Simulation exercises are increasingly being used as a teaching method in the field of undergraduate nursing education. Thus, the present study sought to identify, describe and discuss enablers of the successful implementation of simulation exercises in undergraduate nursing education. Methods This study had a qualitative descriptive design and involved individual interviews conducted between November and December 2018 with six nurse teachers from three different university campuses in Norway. The transcribed interviews were analysed by means of a qualitative thematic analysis. Results The majority of the interviewees wanted to offer more simulation exercises as part of their respective undergraduate nursing education programmes. Moreover, creating a safe environment, facilitating student-centred learning and promoting reflection were all identified by the interviewees as enablers of the successful implementation of simulation exercises. Conclusions The findings of this study indicate that nurse teachers consider simulation to be a valuable teaching method for improving students' learning outcomes. In addition, the findings could guide the future implementation of simulation exercises in undergraduate nursing education. Trial registration ClinicalTrials.gov ID: NCT 04063319 . Protocol ID: 52110 Nursing Students' Recognition of and Response to Deteriorating Patients.